Financial fitness / Muhammad Iqbal Irwan ... [et al.] - Irwan, Muhammad Iqbal; Ghazali, Nazurah; Zainuddin, Nur Syaiera Aqilah; Mohd Zamri, Nur Khairul Izzati; Rahim, Hainnuraqma (Universiti Teknologi MARA, Kedah, 2023)
This project is about introducing innovative ideas for people who have problems in their financial planning. The innovation idea is an online application called Financial Fitness. The issue related to this project where people tend to overspend their money by buying things that are not needed for them and lead them to be extravagant. Mostly, financial bankruptcy always occurs among teenagers. It is because people nowadays prefer to buy luxurious things in order to make them look wealthy without thinking about the consequences if they spend too much money but do not have savings for the future. The purpose of this project was created to help people manage their money in a good way. This Financial Fitness has their own uniqueness which is five functions included. The first one, it would help us to track our expenses. So, people could know where the money spent in a day. Next, Financial Fitness provided us with advice about expenses. From it, we can learn and gain more knowledge about the benefits of saving. Third, it has the expenses Categorization and Analysis. Basically, this function included the analysis percentage of usage money for every category item. Lastly, from this online application people could share their experiences while using this application for motivation to others. This could help people to motivate themselves if they consistently use this application day by day. The way Financial Fitness works is people need to state how much money they want to spend in a day. Then, this application will notify us if they reach the limit of the amount of money stated. By doing so, people will spend their money carefully without wasting it.